Adult sex ratios and their implications for cooperative breeding in birds. (19th September 2017) - Komdeur, Jan; Székely, Tamás; Long, Xiaoyan; Kingma, Sjouke A.
Abstract : Cooperative breeding is a form of breeding system where in addition to a core breeding pair, one or more usually non-breeding individuals provide offspring care. Cooperative breeding is widespread in birds, but its origin and maintenance in contemporary populations are debated. Although deviations in adult sex ratio (ASR, the proportion of males in the adult population) have been hypothesized to influence the occurrence of cooperative breeding because of the resulting surplus of one sex and limited availability of breeding partners, this hypothesis has not been tested across a wide range of taxa. By using data from 188 bird species and phylogenetically controlled analyses, we show that cooperatively breeding species have more male-biased ASRs than non-cooperative species. Importantly, ASR predicts helper sex ratio: in species with more male-biased ASR, helper sex ratio is also more male biased. We also show that offspring sex ratios do not predict ASRs, so that the skewed ASRs emerge during the period when individuals aim to obtain a breeding position or later during adulthood. In line with this result, we found that ASR (among both cooperatively and non-cooperatively breeding species) is inversely related to sex bias in dispersal distance, suggesting that the cost of dispersal is more severe for the further-dispersing sex. As females usually disperse further in birds, this explains the generally male-biased ASR, and in combination with benefits of philopatry for males, this probably explains why ASR is more biased in cooperatively breeding species. Taken together, our results suggest that a sex bias in helping in cooperatively breeding species relates to biased ASRs. We propose that this relationship is driven by sex-specific costs and benefits of dispersal and helping, as well as other demographic factors. Future phylogenetic comparative and experimental work is needed to establish how this relationship emerges. This article is part of the themed issue 'Adult sex ratios and reproductive decisions: a critical re-examination of sex differences in human and animal societies'.